2020
DOI: 10.3389/fpls.2020.01224
|View full text |Cite
|
Sign up to set email alerts
|

Integral Projection Models and Sustainable Forest Management of Agave inaequidens in Western Mexico

Abstract: In México, at least 37 Agave species are extracted from wild populations for producing distilled spirits. This activity involves harvesting mature agaves just before producing their inflorescences, which cancels sexual reproduction of plants used. The increasing demand of agaves spirits in national and international markets is determining a strong pressure on wild populations, most of them lacking adequate management. In addition, the dynamics of agave populations may be affected by natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Some studies have shown that the evaluation of different harvesting techniques can help to improve them. These include harvesting time, season, frequency, a minimum size of individuals harvested, and artificial insertion of seedlings into the population (Ticktin, 2004;Endress et al, 2006;Torres-García et al, 2020). Freckleton et al (2003) simulated E. edulis harvesting during the pre-reproductive and postreproductive seasons and found that the populations tolerated higher levels of palm heart harvesting if it was conducted after the reproductive period, not previously.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that the evaluation of different harvesting techniques can help to improve them. These include harvesting time, season, frequency, a minimum size of individuals harvested, and artificial insertion of seedlings into the population (Ticktin, 2004;Endress et al, 2006;Torres-García et al, 2020). Freckleton et al (2003) simulated E. edulis harvesting during the pre-reproductive and postreproductive seasons and found that the populations tolerated higher levels of palm heart harvesting if it was conducted after the reproductive period, not previously.…”
Section: Figurementioning
confidence: 99%
“…Different management methods have been evaluated, including harvesting time, intensity, frequency, life form, and plant part harvested (Ticktin et al, 2002;Endress et al, 2006;Vallejo et al, 2014). As the harvesting of herbs commonly leads to mortality, influences on demographic parameters are negative and stronger (see Ghimire et al, 2008;Torres-García et al, 2020), while leaf and fruit harvesting on palm and tree species, which do not cause the death of individuals tend to have weaker effects on population demography and be sustainable (see Zuidema and Boot, 2002;Zuidema et al, 2007;Sampaio et al, 2008). In general, harvesting has been shown to negatively affect vital rates and population growth rates (Schmidt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Besides its use in producing natural fibers, A. H11648 could also be utilized for alcoholic beverages [ 2 ], nutraceuticals [ 3 ], and nanocellulose [ 4 ], making it a highly valuable crop. Despite its widely valuable usage, A. H11648 also faces a number of challenges due to its susceptibility to various biotic and abiotic stresses, such as cold temperatures [ 5 ], root rot disease [ 6 ], high temperatures [ 7 ], low rainfall [ 8 ], low aboveground biomass coverage [ 9 ] and agave purple curl leaf disease [ 10 ]. Among these various stresses, agave purple curl leaf disease poses a significant threat to the agave industry as it severely damages the plant’s leaves which are the primary source of its natural fibers and will cause a sharp reduction in leaves production by more than 30% in severe cases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%